Investigation of Metal Matrix Composites Aluminium Reinforced Graphite Particles Produced Using Powder Metallurgy - Nanang Fatchurrohman; Anis Nabilah Binti Mamat; Mutiara Yetrina; Rifki Muhida (Universitas Putra Indonesia YPTK Padang, 2022)
Many industries have been in demand for metal matrix composites (MMC), especially in the aerospace and automotive sectors. The advancement of MMC is being investigated to improve the material's mechanical properties. MMC is a composite material consisting of at least two materials. One of them would act as a matrix, and the other materials would serve as reinforcement. MMC allows for overcoming the specific limitations of metallic and ceramic materials by blending their mutually exclusive property profiles. The main objective of this research is to successfully fabricate aluminium and graphite metal matrix composites using powder metallurgy. In this research, powder metallurgy was used, where aluminium and graphite were blended according to the sample volume ratio. Both graphite and aluminium were in the form of metal powder. Graphite powder with each ratio of volume percentages of 0%, 1.5%, 3%, 4.5%, and 6% was mixed with aluminium powder. The blended material is produced by powder metallurgy via the compaction process using the hydraulic press brake machine. Subsequently, the compacted sample was sintered using a laboratory furnace at 600°C for 4 hours. The mechanical tests show that the highest tensile strength and Young's modulus were obtained by MMC aluminium – 1.5 % volume graphite. While for the highest hardness was achieved by aluminium – 4 % volume graphite.